Glucose/Xylose Co-Fermenting Saccharomyces cerevisiae Increases the Production of Acetyl-CoA Derived n-Butanol From Lignocellulosic Biomass - Lee Yeonjung; Tran, Nguyen Hoang Phuong; 고자경; Gong, Gyeong taek; Um, Young soon; 한성옥; Lee, Sun Mi (Frontiers Research Foundation, 2022)
Efficient xylose catabolism in engineered Saccharomyces cerevisiae enables more economical lignocellulosic biorefinery with improved production yields per unit of biomass. Yet, the product profile of glucose/xylose co-fermenting S. cerevisiae is mainly limited to bioethanol and a few other chemicals. Here, we introduced an n-butanol-biosynthesis pathway into a glucose/xylose co-fermenting S. cerevisiae strain (XUSEA) to evaluate its potential on the production of acetyl-CoA derived products. Higher n-butanol production of glucose/xylose co-fermenting strain was explained by the transcriptomic landscape, which revealed strongly increased acetyl-CoA and NADPH pools when compared to a glucose fermenting wild-type strain. The acetate supplementation expected to support acetyl-CoA pool further increased n-butanol production, which was also validated during the fermentation of lignocellulosic hydrolysates containing acetate. Our findings imply the feasibility of lignocellulosic biorefinery for producing fuels and chemicals derived from a key intermediate of acetyl-CoA through glucose/xylose co-fermentation.